Design and Performance Evaluation of Real‐time Endovascular Interventional Surgical Robotic System with High Accuracy. Issue 5 (15th May 2018) - Wang, Kundong; Chen, Bing; Lu, Qingsheng; Li, Hongbing; Liu, Manhua; Shen, Yu; Xu, Zhuoyan
Abstract: Background: Endovascular interventional surgery (EIS) is performed under a high radiation environment at the sacrifice of surgeons' health. This paper introduces a novel endovascular interventional surgical robot that aims to reduce radiation to surgeons and physical stress imposed by lead aprons during fluoroscopic X‐ray guided catheter intervention. Methods: The unique mechanical structure allowed the surgeon to manipulate the axial and radial motion of the catheter and guide wire. Four catheter manipulators (to manipulate the catheter and guide wire), and a control console which consists of four joysticks, several buttons and two twist switches (to control the catheter manipulators) were presented. The entire robotic system was established on a master–slave control structure through CAN (Controller Area Network) bus communication, meanwhile, the slave side of this robotic system showed highly accurate control over velocity and displacement with PID controlling method. Results: The robotic system was tested and passed in vitro and animal experiments. Through functionality evaluation, the manipulators were able to complete interventional surgical motion both independently and cooperatively. The robotic surgery was performed successfully in an adult female pig and demonstrated the feasibility of superior mesenteric and common iliac artery stent implantation. The entire robotic system met the clinical requirements of EIS. Conclusion: The results show that the system has the ability to imitate the movements of surgeons and to accomplish the axial and radial motions with consistency and high‐accuracy.